Optoelectronic van der Waals heterostructure devices and the growth of C-doped hBN by MBE - James, Tyler S S (2024)
By encapsulating self-assembled layers of optically-active organic molecules between atomically thin insulating layers, van der Waals heterostructures can be fabricated which incorporate these encapsulated molecules between two graphene electrodes. The thin, transparent insulating layers allow the optical properties of the molecules to be investigated through optical excitation, and also for the molecules to be excited by charge carriers tunnelling between the electrodes. The lateral size of these tunnelling devices can be reduced by ∼ 1000× by replacing the graphene electrodes with carbon nanotubes, opening a route for lithography-free nanometre-scale electronic devices. Alternatively, to produce such devices at an industrial scale, the controlled growth of large-area, high-quality 2D materials is required, which requires the use of techniques such as molecular beam epitaxy.